Mood and autobiographical memory: effects on the intensity of school memories - Boyano, José T.; Mora, Juan A. (Anales de Psicología / Annals of Psychology, 2015)
The influence of mood on memory for simple stimuli has been observed frequently. This paper examines the effect of mood on autobiographical memory, going to analyze (1) the presence of the mood-congruent memory effect in school memories and (2) the typical anomalies of the effect. We intend to study the biases that may affect, during retrieval, the subjective rating of relevant events in school history. We used a sample of college students assigned to different groups of mood induction. Three states (happy, sad or neutral mood) were induced by film material having emotional scenes. Memories intensity was recorded by the LIM method. The mood-congruent memory effect has been partial and asymmetric. Our results indicate that participants with happy mood tend to a greater rating of positive and negative events, whereas sad participants tend to more conservative valuations. Neutral-mood participants rated the positive events with a higher level than negative. These data suggest that the mood generates a preferred processing style which modulates the valuation of memories.